Pengaruh Pengetahuan Produk, Tingkat Pemahaman Produk dan Kesadaran Religiusitas Terhadap Minat Menabung di BSI pada Generasi Z - Sari, Mutiara Ardiya; Husaen, Fuad Dhiya Ul (LPPM, 2024)
This research is a quantitative study to determine the influence of product knowledge, level of product understanding and awareness of religiosity on interest in saving at BSI. The population is UIN Raden Mas Said Surakarta students. The sample was taken using the Non Probability Sampling technique with Purposive Sampling Technique through distributing questionnaires and obtained 126 respondents, namely FEBI students who had saved at BSI at least three transactions or who had used BSI products/services. The data was tested using the IBM SPSS Statistics 25 application. The analyzes used included: Validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, t test, F test and determination test (ð‘…2). The results of the t test show that the product knowledge variable has a negative and insignificant effect on interest in saving, the variable level of product understanding has a positive and significant effect on interest in saving, and awareness of religiosity has a positive and significant effect on interest in saving. The results of the F test show that the variables product knowledge, level of product understanding and awareness of religiosity together have a positive and significant effect on interest in saving.